Causes and Prevalence of Tooth Loss among Patients attending Dental Clinics in Gharian, Libya - Awatif Almagtouf; Azah Arara; Esam Shaglouf (AlQalam Journal of Medical and Applied Sciences, 2024)
The aim of this study was to investigate the prevalence, causes of tooth loss, and associated factors among the older adult population attending dental clinics in the city of Gharyan in Libya. A descriptive cross-sectional study conducted among adults who came to private clinics in the city of Gharyan in Libya. There were 160 patients participated in the study. Those that met the inclusion criteria had their data collected via self-administered questionnaires. Computer-assisted techniques used to examine the data (IPMSPSS). The results of the present study indicated that the major cause of tooth loss was dental caries (65.56%), followed by periodontal disease (11.88%). and more teeth loss was in the female than male and increased tooth loss with aging. In conclusion, there was a high prevalence of tooth loss. Females lost more teeth than males. Increased proportion of tooth loss seen in the elderly population. كان الهدف من هذه الدراسة هو التحقيق في انتشار وأسباب فقدان الأسنان والعوامل المرتبطة بها بين كبار السن الذين يرتادون عيادات الأسنان في مدينة غريان في ليبيا. أجريت دراسة وصفية مقطعية بين البالغين الذين جاءوا إلى العيادات الخاصة في مدينة غريان في ليبيا. شارك في الدراسة 160 مريضًا. تم جمع بيانات أولئك الذين استوفوا معايير الإدراج من خلال استبيانات ذاتية الإدارة. تم استخدام تقنيات بمساعدة الكمبيوتر لفحص البيانات (IPMSPSS). أشارت نتائج الدراسة الحالية إلى أن السبب الرئيسي لفقدان الأسنان كان تسوس الأسنان (65.56٪)، يليه مرض اللثة (11.88٪). وكان فقدان الأسنان أكثر لدى الإناث منه لدى الذكور وزيادة فقدان الأسنان مع تقدم العمر. في الختام، كان هناك انتشار كبير لفقدان الأسنان. فقدت الإناث أسنانًا أكثر من الذكور. زادت نسبة فقدان الأسنان لدى كبار السن